The IMPLEMENTATION OF ALFABET BOX EDUCATIVE GAMES TO IMPROVE LANGUAGE SKILLS - Wiresti, Ririn Dwi; Vionitta Wibowo , Devi (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2021)
Language development is an important development to be stimulated properly, because it is this development that lead children to social development that can affect emotions and even cognitive. If this language development is not stimulated optimally then the child can experience developmental stagnation. The importance of language development is not accompanied by adequate educational learning tools. So researchers want to know how to implement the Alphabet box game to improve children's language development. This research is a qualitative research with a description method with the mother teacher data source and class B1 BA Restu 1 Malang. Data were collected in 3 ways, namely interviews, observation, and documentation. So that the results of in-depth, detailed, and credible research, researchers in miles and hub analysis techniques include data collection, data presentation, data reduction, and concluding. The results of this study indicate that the implementation of an alphabet box educational game tool can improve children's language development accompanied by the mother of the teacher.